Farm Animals Diseases, Recent Omic Trends and New Strategies of Treatment - Estela Quiroz-Castañeda, Rosa (IntechOpen, 2018)
The scope of this book is to present the most recent trends based on omic analyses of microorganisms causing diseases in farm animals and how these approaches result in new strategies of treatment. The topics in this book include fasciolosis, avian coccidiosis, bovine anaplasmosis, tick-borne diseases, and babesiosis, among others. This book presents the recent advances in the omic field with an emphasis on how these analyses have led researchers to know the mechanisms that pathogens use to invade and colonize the host cell of farm animals. In this way, new treatments of control and prevention can be employed.